HIV and coronary artery calcium score: comparison of the Hawaii Aging with HIV Cardiovascular Study and Multi-Ethnic Study of Atherosclerosis (MESA) cohorts. Issue 4 (August 2015) - Chow, Dominic; Young, Rebekah; Valcour, Nicole; Kronmal, Richard A.; Lum, Corey J.; Parikh, Nisha I.; Tracy, Russell P.; Budoff, Matthew; Shikuma, Cecilia M.
Abstract : Objectives: To determine the association of HIV, immunologic, and inflammatory factors on coronary artery calcium (CAC), a marker of subclinical atherosclerosis. Methods: Cross-sectional study comparing baseline data of males from Hawaii Aging with HIV – Cardiovascular Study (HAHCS) with the Multi-Ethnic Study of Atherosclerosis (MESA) cohort. The cohorts were pooled to determine effects of HIV on CAC and explore immunologic and inflammatory factors that may explain development of CAC in HIV. Multivariable regression models compared CAC prevalence in HAHCS with MESA adjusting for coronary heart disease (CHD) risk profiles. Results: We studied 100 men from HAHCS and 2733 men from MESA. Positive CAC was seen in 58% HAHCS participants and 57% MESA participants. Mean CAC was 260.8 in HAHCS and 306.5 in MESA. Using relative risk (RR) regression, HAHCS participants had a greater risk (RR = 1.20, P  < 0.05) of having positive CAC than MESA when adjusting for age, smoking status, diabetes, antihypertensive therapy, BMI, systolic blood pressure, total cholesterol, and HDL cholesterol. Among participants with positive CAC, HIV infection was not associated with larger amounts of CAC. Among HAHCS participants, current HIV viral load, CD4, length of HIV, interleukin 6 (IL-6), fibrinogen, C-reactive protein (CRP), and D-dimer were not associated with the presence or amount of CAC. Discussion: HIV was independently associated with a positive CAC in men with increased likelihood occurring between 45 and 50 years of age. Current HIV viral load, CD4 count, length of HIV, and inflammatory markers were unrelated to either presence or amount of CAC.